APLIKASI AKUNTANSI PERSEDIAAN BARANG DAGANG (Studi Kasus: PT. Denpoo Mandiri Lampung) - Marlia Sari (KOLONI, 2022)
Inventory of goods is a very important main component in a company, because inventory will be sold continuously for the survival of the company. So it can be said that in almost every trading company, inventory is a fairly large asset when compared to other current assets. Trading companies are closely related to the availability of inventory in the warehouse to maintain sales operations in the company. Problems that often occur in inventory include the risk of loss of goods, and errors in recording inventory. Data collection methods used in this study were observation, interviews and literature study, and the system development method was Extreme Programming. The application design uses use cases, class diagrams, and activities. This research produces a Merchandise Inventory Accounting Application that can make it easier to present accurate and timely inventory report data, make it easier to input the data needed in processing inventory, and simplify admin performance in archiving inventory data  Keywords: Accounting Applications, Merchandise Inventory, Extreme Programming